Circular Economy in Waste Management Systems: Technological Innovations for Sustainable Resource Recovery and Waste Minimization - Obed Patiung; Olivia Jimenez; Luis Ramirez (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Rapid urbanization and industrial growth have exacerbated waste generation worldwide, challenging traditional waste management systems and threatening environmental sustainability. Linear disposal practices often lead to resource depletion, pollution, and increased greenhouse gas emissions. Circular economy principles offer a strategic framework to transform waste streams into valuable resources, emphasizing reuse, recycling, and technological innovation for sustainable management. Purpose. This study aims to investigate how technological innovations can enable circular economy practices in waste management, enhance resource recovery, and minimize environmental impacts. The research evaluates the effectiveness of advanced waste treatment technologies, process optimization, and material recovery strategies across diverse urban and industrial contexts. Method. A mixed-methods approach was employed, combining systematic literature review, technical performance analysis, and comparative case studies of innovative waste management systems. Data on recycling efficiency, resource recovery rates, energy recovery, and environmental impacts were collected and analyzed to assess the practical contribution of technological interventions. Results. Results indicate that integration of automation, smart sorting, bioconversion, and advanced material recovery significantly improves resource efficiency and reduces landfill dependency. Case studies demonstrate measurable reductions in waste volumes, improved material circularity, and enhanced sustainability outcomes. Conclusion. The study concludes that technological innovation is critical for operationalizing circular economy principles in waste management systems, providing both environmental and economic benefits while supporting sustainable urban development.